Characterization of Protease from Endophytic Fungi Fusarium sp. JE-DP4a - Hastuty, Aerma; Herawati, Irma; Pikoli, Megga Ratnasari (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
Protease is a catalytic enzyme that catalyzes a proteolysis process and breaks down a protein into smaller polypeptides or amino acids. Endophytic fungi can produce bioactive compounds, one of which is protease enzymes. The papaya leaf endophytic fungi used in this study was Fusarium sp. strain JE-DP4a. This study was conducted to determine the characterization of protease from endophytic fungi Fusarium sp. strain JE-DP4a with variations in incubation temperature of 30, 37, and 44oC and pH variation of 5.5-8. Measurement of protease enzyme activity using a spectrophotometer UV-Vis at 280 nm. Based on the research results, the highest protease activity produced at a temperature of 44oC is 53.78 U/mL, and specific activity is 17.31 U/mg protein. Protease activity at pH 7 shows the highest was 46.72 U/mL.Thus it is ably concluded that the protease produced by Fusarium sp. strain JE-DP4a belongs to the neutral protease group.